Li3PO4 surface coating on Ni-rich LiNi0.6Co0.2Mn0.2O2 by a citric acid assisted sol-gel method: Improved thermal stability and high-voltage performance - Lee, Suk-Woo; Kim, Myeong-Seong; Jeong, Jun Hui; Kim, Dong-Hyun; Chung, Kyung Yoon; Roh, Kwang Chul; Kim, Kwang-Bum (ELSEVIER SCIENCE BV, 2017)
A surface coating of Li3PO4 was applied to a Ni-rich LiNi0.6Co0.2Mn0.2O2 (NCM) material to improve its thermal stability and electrochemical properties via a citric acid assisted sol-gel method. The addition of citric acid effectively suppressed the instant formation of Li3PO4 in solution, resulting in successful coating of the NCM surface. The improved thermal stability of NCM after Li3PO4 surface coating was demonstrated by differential scanning calorimetry (DSC) analysis and in situ time-resolved X-ray diffraction (TR-XRD). In particular, the TR-XRD results showed that the improved thermal stability after Li3PO4 surface coating originates from suppression of the phase transition of charged NCM at high temperatures. Furthermore, the charge discharge tests demonstrated that Li3PO4-coated LiNi0.6Co0.2Mn0.2O2 (LP-NCM) has excellent electrochemical properties. LP-NCM exhibited a specific capacity of 192.7 mAh g(-1), a capacity retention of 44.1% at 10 C, and a capacity retention of 79.7% after 100 cycles at a high cut-off voltage of 4.7 V; these values represent remarkably improved electrochemical properties compared with those of bare NCM. These improved thermal and electrochemical properties were mainly attributed to the improvement of the structural stability of the material and the suppression of the interface reaction between the cathode and the electrolyte owing to the Li3PO4 coating. (c) 2017 Elsevier B.V. All rights reserved.
Keywords: LITHIUM-ION BATTERIES; ENHANCED ELECTROCHEMICAL PERFORMANCE; CATHODE MATERIAL; SECONDARY BATTERIES; CYCLING PERFORMANCE; IMPEDANCE SPECTRA; LICOO2; LINI1/3CO1/3MN1/3O2; ELECTRODES; CAPACITY